2021
DOI: 10.1172/jci.insight.142976
|View full text |Cite
|
Sign up to set email alerts
|

Fecal host biomarkers predicting severity of Clostridioides difficile infection

Abstract: Potential financial conflict of interest: D. Vinh is supported by the Clinician-Scientist Scholar Junior 2 program of the Fonds de la recherche en santé du Québec and has received research support from Cidara Therapeutics, CSL Behring and Janssen Pharmaceutical, and consulting or speaker honoraria from CSL Behring, Novartis Canada, and UCB Biosciences GmbH. None of these entities were involved in any aspect of the research in this manuscript. D. Vinh has a patent application pending (EFS ID: 40101099), unrelat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…Essentially, proteins are separated by liquid chromatography and detected by mass spectrometry. Interesting candidates are identified following rigorous statistical analysis of MS/MS data for further structural and biological information . Although top-down proteomics was more of a fringe method with limited application to clinical samples, top-down approaches are now gaining more and more popularity in forensics and doping control. The point of this Perspective is thus to highlight how top-down proteomics can contribute to toxicology research in public health and to the battle against sports doping.…”
Section: Lc-ms/(ms)-based Proteomicsmentioning
confidence: 99%
“…Essentially, proteins are separated by liquid chromatography and detected by mass spectrometry. Interesting candidates are identified following rigorous statistical analysis of MS/MS data for further structural and biological information . Although top-down proteomics was more of a fringe method with limited application to clinical samples, top-down approaches are now gaining more and more popularity in forensics and doping control. The point of this Perspective is thus to highlight how top-down proteomics can contribute to toxicology research in public health and to the battle against sports doping.…”
Section: Lc-ms/(ms)-based Proteomicsmentioning
confidence: 99%
“…The relative abundance of alpha-1-antitrypsin was significantly higher in non-severe than severe patients ( p = .028), identifying it as a putative biomarker of severity. 82 …”
Section: Microbiologic Factors Associated With CDI Outcomesmentioning
confidence: 99%
“…The relative abundance of alpha-1-antitrypsin was significantly higher in non-severe than severe patients (p = .028), identifying it as a putative biomarker of severity. 82 Another strategy to profile the association between immune response and CDI severity is to measure systemic biomarkers in circulation. One of the early studies (78 cases; 8 of them met CDC severity criteria) found that severe patients had significantly elevated levels of IL-8 [odds ratio (OR) = 5.92; 95% CI = 1.13-31.1] and IL-6 (OR = 3.12; 95% CI = 1.05-9.28).…”
Section: Therapeutic Advances In Gastroenterology 14mentioning
confidence: 99%
“…Using this method, a recent paper by Golizeh identified fecal host proteins that may be useful in differentiating C. difficile infection from other causes of diarrhea and seem to correlate with clinical severity [62]. Alpha-2 macroglobulin and matrix metalloproteinase-7 are produced by the intestinal mucosal epithelium and levels may correlate with disease severity [62]. Protection from inflammation is associated with the presence of alpha-1-antitrypsin and levels of this serine protease inhibitor negatively correlate with disease severity [62].…”
Section: Using Biomarkersmentioning
confidence: 99%
“…Alpha-2 macroglobulin and matrix metalloproteinase-7 are produced by the intestinal mucosal epithelium and levels may correlate with disease severity [62]. Protection from inflammation is associated with the presence of alpha-1-antitrypsin and levels of this serine protease inhibitor negatively correlate with disease severity [62].…”
Section: Using Biomarkersmentioning
confidence: 99%